MARKETING DIGITALIZATION READINESS OF MSMES ASSISTED BY THE BANDUNG CITY CHAMBER OF COMMERCE AND INDUSTRY - Panggelo, Sophia Laurens; Yarangga, Rosani; Rashela, Windy (PT. Altin Riset Publishing, 2024)
This research aims to determine marketing digitalization readiness in Bandung City Chamber of Commerce and Industry MSMEs. This study used a descriptive quantitative method and questionnaires to 82 MSME respondents. The data was processed using SPSS 25 and formulas to calculate the Technology Readiness Index (TRI). The TRI value calculation shows that the MSMEs' readiness is at the high technology readiness level. This conclusion was obtained from the total score of TRI 4.10. From the results, the innovative variable has the lowest value. To increase the value of the innovative variable, researchers advise respondents to have the courage to make innovations and changes, no matter how small, such as trying to use an e-commerce platform to expand market reach so that they can increase sales significantly.